Environmental science : a study of interrelationships - Enger, Eldon D.; Spoolman, Scott (New York : McGraw Hill Education, 2013)
Presents the approach and reading level that cover the basic concepts without overloading students. This book provides a historical perspective, information on economic and political realities, discuss the role of different social experiences, and integrate this with the crucial science to describe the natural world and how we affect it.
Human And Sustainability: An Overview -- Ecology And Sustainability -- Sustaining Biodiversity -- Sustaining Resources And Environmental Quality -- Sustaining Human Societies.
Includes bibliographical references and index.
Keywords: ENVIRONMENTAL SCIENCES